Evaluation of a multicomponent intervention consisting of education and feedback to reduce benzodiazepine prescriptions by general practitioners: The BENZORED hybrid type 1 cluster randomized controlled trial. - Caterina Vicens; Alfonso Leiva; Ferran Bejarano; Ermengol Sempere-Verdú; Raquel María Rodríguez-Rincón; Francisca Fiol; Marta Mengual; Asunción Ajenjo-Navarro; Fernando Do Pazo; Catalina Mateu; Silvia Folch; Santiago Alegret; et al. (PLoS Medicine, 2022)
Background Current benzodiazepine (BZD) prescription guidelines recommend short-term use to minimize the risk of dependence, cognitive impairment, and falls and fractures. However, many clinicians overprescribe BZDs and chronic use by patients is common. There is limited evidence on the effectiveness of interventions delivered by general practitioners (GPs) on reducing prescriptions and long-term use of BZDs. We aimed to evaluate the effectiveness of a multicomponent intervention for GPs that seeks to reduce BZD prescriptions and the prevalence of long-term users. Methods and findings We conducted a multicenter two-arm, cluster randomized controlled trial in 3 health districts in Spain (primary health centers [PHCs] in Balearic Islands, Catalonia, and Valencian Community) from September 2016 to May 2018. The 81 PHCs were randomly allocated to the intervention group (n = 41; 372 GPs) or the control group (n = 40; 377 GPs). GPs were not blinded to the allocation; however, pharmacists, researchers, and trial statisticians were blinded to the allocation arm. The intervention consisted of a workshop about the appropriate prescribing of BZDs and tapering-off long-term BZD use using a tailored stepped dose reduction with monthly BZD prescription feedback and access to a support web page. The primary outcome, based on 700 GPs (351 in the control group and 349 in the intervention group), compared changes in BZD prescriptions in defined daily doses (DDDs) per 1,000 inhabitants per day after 12 months. The 2 secondary outcomes were the proportion of long-term users (≥6 months) and the proportion of long-term users over age 65 years. Intention-to-treat (ITT) analysis was used to assess all clinical outcomes. Forty-nine GPs (21 intervention group and 28 control group) were lost to follow-up. However, all GPs were included in the ITT analysis. After 12 months, there were a statistically significant decline in total BZD prescription in the intervention group compared to the control group (mean difference: -3.24 DDDs per 1,000 inhabitants per day, 95% confidence interval (CI): -4.96, -1.53, p < 0.001). The intervention group also had a smaller number of long-term users. The adjusted absolute difference overall was -0.36 (95% CI: -0.55, -0.16, p > 0.001), and the adjusted absolute difference in long-term users over age 65 years was -0.87 (95% CI: -1.44, -0.30, p = 0.003). A key limitation of this clustered design clinical trial is the imbalance of some baseline characteristics. The control groups have a higher rate of baseline BZD prescription, and more GPs in the intervention group were women, GPs with a doctorate degree, and trainers of GP residents. Conclusions A multicomponent intervention that targeted GPs and included educational meeting, feedback about BZD prescriptions, and a support web page led to a statistically significant reduction of BZD prescriptions and fewer long-term users. Although the effect size was small, the high prevalence of BZD use in the general population suggests that large-scale implementation of this intervention could have positive effects on the health of many patients. Trial registration ISRCTN ISRCTN28272199.